Sejarah Kurikulum di Indonesia - Iramdan -; Lengsi Manurung (Jurnal Ilmiah Wahana Pendidikan, 2019)
The aimof the writing article is to understand more about the curriculum in Indonesia from the Dutch era until the 2013 curriculum. The curriculum is an important element in all forms and models of education. In a curriculum education system it is dynamic and changes and development must always be carried out in order to be able to keep up with the developments and challenges of the times. The history of curriculum in Indonesia has gone a long way, history notes that changes began in the era of Dutch colonialism, the era of Japanese colonialism, the era of the Old Order (curriculum 1947, curriculum 1952, curriculum 1964), the era of the New Order (curriculum 1968, 1975 curriculum, 1984 curriculum, 1994 curriculum), and the era of the Reformation (curriculum 2004 competency-based curriculum (CBC), education unit level curriculum (KTSP), curriculum 2013).